The "black evil" affecting patients with diabetes: a case of rhino orbito cerebral mucormycosis causing Garcin syndrome - Narayanan S; Panarkandy G; Subramaniam G; Radhakrishnan C; Thulaseedharan NK; Manikath N; Ramaswamy S; Radhakrishnan S; Ekkalayil D (Infection and Drug Resistance, 2017)
Santhosh Narayanan,1 Geetha Panarkandy,1 Gomathy Subramaniam,2 Chandni Radhakrishnan,1 NK Thulaseedharan,1 Neeraj Manikath,1 Sreejith Ramaswamy,1 Suma Radhakrishnan,3 Danish Ekkalayil1 1Department of General Medicine, 2Department of Radiodiagnosis, 3Department of Otorhinolaryngology, Government Medical College, Kozhikode, Kerala, India Abstract: Mucormycosis is a life-threatening infection affecting patients with diabetes. It is an angioinvasive disease often resistant to treatment with a debilitating course and high mortality. Here, we report a case of a 45 year old woman with type 2 diabetes mellitus who presented to us with history of right-sided ptosis and facial palsy, and subsequently developed loss of vision and palatal palsy. She was in diabetic ketoacidosis. Nervous system examination revealed involvement of right second, third, fourth, sixth, seventh, ninth, and tenth cranial nerves, suggestive of Garcin syndrome. The hard palate had been eroded with formation of black eschar. Computed tomography of paranasal sinuses revealed right maxillary and ethmoid sinusitis, with spread of inflammation to infratemporal fossa and parapharynygeal neck spaces. Debridement of sinus mucosa was done, and culture of the same yielded growth of rhizopus species. Histopathological examination of the tissue showed angioinvasion and fungal hyphae suggestive of mucormycosis. She was treated with amphotericin B, posaconazole, and periodic nasal sinus debridement, but her general condition worsened after 8 weeks due to secondary sepsis and she succumbed to death. Keywords: diabetes, rhinoorbitocerebral, mucormycosis, garcin syndrome